2002
DOI: 10.1046/j.1469-8137.2002.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular characterization of NADP‐glutamate dehydrogenase from the ectomycorrhizal fungus Tuber borchii

Abstract: Summary• NADP-glutamate dehydrogenase (NADP-GDH) from Tuber borchii was purified and the corresponding gene was cloned in order to elucidate the physiological role of the enzyme in this ectomycorrhizal fungus.• NADP-GDH was purified using an anion-exchange column followed by affinity chromatography. The complete gene was cloned from a 30-d-old-mycelium cDNA library and characterized.• T. borchii NADP-GDH appears to be physically and kinetically similar to those from other fungi and the deduced amino acid seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 53 publications
0
19
0
1
Order By: Relevance
“…A number of genes coding for inorganic N transporters and N assimilation enzymes have been isolated from these organisms (Guescini et al, 2003;Jargeat et al, 2000Jargeat et al, , 2003Javelle et al, 2001Javelle et al, , 2003bJuuti et al, 2004;Montanini et al, 2002Montanini et al, , 2003Vallorani et al, 2002). Most of them display the same kind of N status responsiveness previously documented in non-mycorrhizal fungi (Magasanik and Kaiser, 2002;Marzluf, 1997).…”
Section: Introductionmentioning
confidence: 93%
“…A number of genes coding for inorganic N transporters and N assimilation enzymes have been isolated from these organisms (Guescini et al, 2003;Jargeat et al, 2000Jargeat et al, , 2003Javelle et al, 2001Javelle et al, , 2003bJuuti et al, 2004;Montanini et al, 2002Montanini et al, , 2003Vallorani et al, 2002). Most of them display the same kind of N status responsiveness previously documented in non-mycorrhizal fungi (Magasanik and Kaiser, 2002;Marzluf, 1997).…”
Section: Introductionmentioning
confidence: 93%
“…In practice, Govindarajulu et al [20] demonstrated N assimilation in the ERM via the GS/GOGAT pathway by measuring mRNA levels for key enzymes in the ERM and IRM tissues with quantitative real-time polymerase chain reactions. They also demonstrated the expression of a putative nicotinamide adenine dinucleotide (NAD)-dependent glutamate dehydrogenase (GDH) gene, which is down-regulated in the ERM tissues supplied with either 3 NO − or NH 4 + in the fungal compartment, consistent with this enzyme playing a catabolic role [21] . Also they found the involvement of the catabolic arm of the urea cycle in transcript levels of genes with a high similarity to known ornithine aminotransferase, urease accessory protein and NH 4 + transporters which are preferentially expressed in the IRM.…”
mentioning
confidence: 93%
“…This renewed perception of the ecological importance of ectomycorrhizae has revived efforts to elucidate the molecular processes underlying nitrogen assimilation and the related starvation stress responses in ectomycorrhizal fungi [13][14][15]. A number of genes coding for ammonium transporters and nitrogen assimilation enzymes have been isolated from these organisms [16][17][18][19][20][21][22]. In contrast, only one gene coding for an as yet functionally uncharacterized NT has been identified so far in a mycorrhizal fungus, the basidiomycete Hebeloma cylindrosporum [23].…”
Section: Introductionmentioning
confidence: 99%